Hypospadias with its Surgical Management: A Comprehensive Review of Surgical Disease in Children - Akhtar, Shavez; Vaidya, Umesh A (Journal of Neonatal Surgery, 2025)
Hypospadias is one of the most common congenital anomalies affecting the male genital tract, with an estimated prevalence of 1 in 150 to 300 male births worldwide. This comprehensive review examines the current state of knowledge regarding hypospadias epidemiology, classification systems, surgical techniques, outcomes, and complications.A systematic literature search was conducted across PubMed, Google Scholar, and relevant pediatric urology journals from 2015 to 2025. Studies were selected based on relevance to hypospadias surgical management, outcome measures, and evidence quality.The tubularized incised plate (TIP) urethroplasty remains the most widely performed technique for distal hypospadias, with fistula rates ranging from 5-10%. Two-stage repairs, particularly the Bracka technique, demonstrate superior outcomes for proximal hypospadias with success rates of approximately 90%. Overall reoperation rates reach 48.2%, with complications occurring most frequently within the first three months post-surgery. Patient satisfaction rates range from 86-92%, though long-term functional outcomes require further investigation. Modern hypospadias surgery has evolved significantly, with standardized classification systems enabling better patient selection and outcome prediction. Multidisciplinary approaches incorporating preoperative hormonal stimulation, refined surgical techniques, and structured follow-up protocols are essential for optimizing outcomes in this challenging patient population.